2013
DOI: 10.2460/ajvr.74.6.839
|View full text |Cite
|
Sign up to set email alerts
|

Field study of the comparative efficacy of gamithromycin and tulathromycin for the control of undifferentiated bovine respiratory disease complex in beef feedlot calves at high risk of developing respiratory tract disease

Abstract: The efficacy of gamithromycin did not differ from that of tulathromycin for all outcomes except morbidity rate; calves administered gamithromycin had a higher BRDC morbidity rate than did calves administered tulathromycin. On the basis of the bioequivalence limits established for this dataset, gamithromycin was considered equivalent to tulathromycin for the control of BRDC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
(29 reference statements)
1
10
1
Order By: Relevance
“…Several authors have reported on the efficacy of tulathromycin in calves, as a prophylactic and metaphylactic drug for the prevention of pneumonia, and also at therapeutic dosages to treat calves with clinical signs of disease (Godinho et al, 2005a,b;Robb et al, 2007;Schunicht et al, 2007;Step et al, 2007;Nickell et al, 2008;Perrett et al, 2008;Van Donkersgoed et al, 2008Rerat et al, 2012;Torres et al, 2013). In addition, Wellman and O'Connor (Wellman & O'Connor, 2007) undertook by meta-analysis a review of the then available clinical literature on tulathromycin, based on 21 manuscripts; comparing tulathromycin with tilmicosin, the summary Mantel-Haenszel relative risk for re-treatment of bovine respiratory disease was 0.51 (95% confidence interval 0.45-0.57), that is an approximately 50% reduction in risk for tulathromycin compared to tilmicosin.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported on the efficacy of tulathromycin in calves, as a prophylactic and metaphylactic drug for the prevention of pneumonia, and also at therapeutic dosages to treat calves with clinical signs of disease (Godinho et al, 2005a,b;Robb et al, 2007;Schunicht et al, 2007;Step et al, 2007;Nickell et al, 2008;Perrett et al, 2008;Van Donkersgoed et al, 2008Rerat et al, 2012;Torres et al, 2013). In addition, Wellman and O'Connor (Wellman & O'Connor, 2007) undertook by meta-analysis a review of the then available clinical literature on tulathromycin, based on 21 manuscripts; comparing tulathromycin with tilmicosin, the summary Mantel-Haenszel relative risk for re-treatment of bovine respiratory disease was 0.51 (95% confidence interval 0.45-0.57), that is an approximately 50% reduction in risk for tulathromycin compared to tilmicosin.…”
Section: Introductionmentioning
confidence: 99%
“…Within each pair, one calf was treated with a single dose of gamithromycin o (6.0 mg/ kg [2 mL/50 kg], SC) and the other was treated with a single dose of tulathromycin p (2.5 mg/kg [1.25 mL/50 kg], SC) on the basis of a treatment randomization schedule that was created for each feedlot in a manner described. 16 The treatments were injected (maximum volume of antimicrobial, 10 mL/injection site) in the neck region cranial to the shoulder joint by a study investigator, and treatments were administered on the same side of the body for all calves within a given feedlot.…”
Section: Methodsmentioning
confidence: 99%
“…For each outcome variable for which no significant difference was detected between the 2 treatment groups via classical hypothesis testing, bioequivalence limits were calculated as described. 16 Statistical software q was used to perform all analyses. Methods used to estimate degrees of freedom, adjust the estimation of SEMs, and perform pairwise comparisons were as described.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These agents often produce mild clinical to severe clinical signs and death within 24 to 36 hours or may cause permanent lung damage as fibrosis, adhesions, and/or abscesses, in chronic cases, which will impact performance. That is why early recognition and treatment of BRDC are so important [3], [4] & [5]. However, the affected calves exhibiting signs of fever, depression, off food, separate themselves from the rest of the pen, abnormal nasal discharge, cough, and abnormal lung sound [6][7].…”
Section: Introductionmentioning
confidence: 99%